CRIMINOLOGICAL CHARACTERISTICS OF CRIMES COMMITTED AT CONSUMER MARKET, AND CONDITIONS OF COUNTERACTION TO THEM - S. Suleimanov (Russian Journal of Economics and Law)
The article views the issues referring to additions and amendments to the functioning legislation regulating the entrepreneurship activity.